Cardiovascular effect of the immune enhancing herbs - Yuan, Shi-Min (Progress in Nutrition, 2018)
Objectives: The nutrients, active ingredients and pharmacological effects of the immune enhancing herbs have drawn attention. The pertinent aspects of the edible immune enhancing products are a topic of interest, and their cardiovascular effects warrant deeper understanding. Methods: The data sources of this study are based on retrieval of the literature of edible immune enhancing products from the MEDLINE and China Biology Medicine Disc (CBMdisc) databases between 1990 and 2016. Results: Immune enhancing herbs work by nourishing white blood cells, protecting against toxins, and influencing the innate immune system through alkaloids, flavonoids, saponins and polysaccharides, etc. The cardiovascular effects of the immune enhancing products are closely related to the active ingredients that they contain. They have a common anti-oxidant effect against myocardial ischemia. The anti-angiotensin converting enzyme, calcium antagonistic, acetycholine-like and non quinidine-like, cellular contractility-strengthening and platelet aggregation inhibiting properties endow them with anti-hypertensive, myocardial protective, anti-arrhythmic, inotropic and lipid-lowering effects. Conclusions: Researches on the active ingredients and cardiovascular effects of the edible immune enhancing products extend their pharmacological application spectrum to heart disorders. The pharmacological effects are closely related to the active ingredients that they contain. Further research on the active ingredients of the products would facilitate the mechanistic study and subsequent drug discovery.